Millennial Parents’ Skepticism Toward Modern Parenting Approaches in Early Childhood Education - Ansharul Fuqaha' (Institut Agama Islam Negeri Madura, 2026)
In the midst of shifting parenting paradigms, early childhood has become a critical arena where millennial parents must navigate between traditional expectations and modern approaches. This study aims to explore the skepticism of millennial parents toward modern parenting science and to examine the influencing factors, including personal experiences, traditional cultural norms, media exposure, and the psychological impacts that arise. Employing a qualitative approach with a case study method, data were collected through in-depth interviews, participatory observation, and documentation involving fifteen millennial parents living in a traditional community setting. The findings reveal that childhood experiences serve as a primary reference point in evaluating the effectiveness of modern parenting approaches. Local cultural values that emphasize collectivism, physical closeness, and family hierarchy reinforce resistance to new parenting paradigms. Meanwhile, exposure to digital media provides broad access to parenting information but also leads to confusion due to the overwhelming and often contradictory content. This skepticism results in inconsistent parenting practices, social pressure, and internal conflicts that contribute to emotional fatigue and psychological strain among parents. The study concludes that skepticism toward modern parenting science is not a form of outright rejection, but rather an adaptive response to the mismatch between theoretical ideals and the socio-cultural realities faced by parents. Therefore, the dissemination of modern parenting approaches must be contextualized, participatory, and sensitive to the lived experiences and cultural values of millennial parents.